2019
DOI: 10.1136/bmj.l665
|View full text |Cite
|
Sign up to set email alerts
|

Use of postmenopausal hormone therapy and risk of Alzheimer’s disease in Finland: nationwide case-control study

Abstract: Objectives To compare the use of hormone therapy between Finnish postmenopausal women with and without a diagnosis for Alzheimer’s disease. Design Nationwide case-control study. Setting Finnish national population and drug register, between 1999 and 2013. Participants All postmenopausal women (n=84 739) in Finland who, between 1999 and 2013, received a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
125
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 37 publications
10
125
1
1
Order By: Relevance
“…In contrast, two cross‐sectional studies reported higher odds ratios of dementia with number of pregnancies 30,31 . Furthermore, exogenous estrogens did not affect incident dementia in our study, contrary to previous studies reporting that exogenous estrogens reduce 3,4 or increase 6,32 dementia risk.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, two cross‐sectional studies reported higher odds ratios of dementia with number of pregnancies 30,31 . Furthermore, exogenous estrogens did not affect incident dementia in our study, contrary to previous studies reporting that exogenous estrogens reduce 3,4 or increase 6,32 dementia risk.…”
Section: Discussioncontrasting
confidence: 99%
“…For a more complete overview of the UKB data acquisition, neuroimaging protocol, and validation, see work by Miller 27 and Alfaro-Almagro 28 . In brief, diffusion-weighted images were acquired at b=1000 and 2000 s/mm 2 along with 50 noncoplanar diffusion directions per diffusion shell with 5 b=0 s/mm 2 (and 3 b=0 blip-reversed) using a standard ('monopolar') Stejskal-Tanner pulse sequence (voxel dimension: (2 mm) 3 isotropic, field of view: 104x104x72 mm; gradient timings: small delta=21.4 ms, big delta=45.5 ms) for a total imaging time of 7 minutes.…”
Section: Mri Processingmentioning
confidence: 99%
“…On average, women above 40 years of age are at a greater risk of developing AD than age-matched men. Endogenous and exogenous estrogen levels also influence this risk 3,4 . Still, we know very little about how sex hormone levels affect brain aging.…”
Section: Introductionmentioning
confidence: 99%
“…A linked study (doi:10.1136/bmj.l665) by Savolainen-Peltonen and colleagues in this week’s The BMJ explores associations between menopausal hormone therapy and risk of Alzheimer’s disease 1. Two thirds of patients with Alzheimer’s disease are women 2.…”
mentioning
confidence: 99%
“…A parallel hypothesis applies to hormone therapy and cardiovascular health. Although available evidence suggests that the overall health benefits outweigh the risks in younger postmenopausal women without contraindications,6 should these women be concerned about an increased risk of dementia, as the case-control study by Savolainen-Peltonen and colleagues suggests?1…”
mentioning
confidence: 99%